Double-Edged Sword of Strategic Agility: Capability Drivers of Sustainable Competitive Advantage in Higher Education - Ema Trisnawati; Barkah Barkah; Wenny Pebrianti (PT. Riset Press International, 2026)
The growing demand for quality higher education in developing countries has placed private higher education institutions (PHEIs) under increasing pressure to build and sustain competitive advantage. Yet, how internal strategic capabilities collectively shape long-term competitiveness in these institutions remains insufficiently explored. This study investigates the influence of research capacity and marketing capability on sustainable competitive advantage among PHEIs in Indonesia, with strategic agility serving as a mediating variable. A quantitative explanatory design was adopted, drawing on survey data from 318 institutional leaders and analyzed through PLS-SEM. The findings reveal that both research capacity (β = 0.509, p < 0.001) and marketing capability (β = 0.455, p < 0.001) exert positive and significant direct effects on sustainable competitive advantage. However, strategic agility exhibits a significant negative direct effect (β = –0.367, p < 0.001), suggesting that excessive short-term responsiveness may undermine institutional stability. The mediation analysis indicates that strategic agility positively mediates the relationship between research capacity and competitive advantage, but negatively mediates the marketing capability–competitive advantage path. These findings contribute to the resource-based view and dynamic capabilities literature by demonstrating the nuanced role of strategic agility in higher education settings, offering practical guidance for PHEI leaders seeking to balance adaptability with long-term institutional coherence. The study extends the marketing capability literature by showing where market sensing strength becomes self-defeating, and offers PHEI leaders a clearer rule: deploy marketing capability for direct positioning, but moderate the speed and frequency of the strategic shifts it triggers.